Management of communited patellar fracture with combined Tension Band Wiring Technique and Encirclage - Desai, Tarun V.; Moradiya, Niravkumar P. (International Journal of Research in Orthopaedics, 2018)
Background: The objective of the study was to evaluate functional results of combined encirclage wiring and tension band fixation in comminuted patellar fractures. Methods: This is a prospective study of 15 patients treated with this method. All fractures described herein were classified as 45-C3 (based on Orthopaedic Trauma Association classification) and were fixed with encirclage wire and tension band wire proximally looped through the quadriceps tendon and distally through the patellar ligament in a figure-of-eight configuration. Knee function was evaluated using the Rasmussen scores at final follow-up. Results: 13 patients gained up to 90 degrees of active flexion at the end of the first week. 4 patients had 10–15 degrees of extensor lag at the end of the first week which improved after vigorous physiotherapy and none of them had any residual extensor lag at the subsequent follow-up. Two patients developed superficial infection. All fractures united at the end of 12 weeks. One patient underwent a second surgery; due to implant related complications. Malunion or non-union was not noted in any of the cases. The average Rasmussen scores was 27.9 out of 30 (range, 27–29). Conclusions: The tension band technique combined with cable encirclage for treatment of communited fractures of patella is a simple and technically less demanding operative technique producing a rigid fixation, stable osteosynthesis and minimal injury to the tendon. It can be done with easily available implants.